The Development of a Web-Based Electronic Module for Fiction Prose Appreciation - Halimah, H; Yulianeta, Y; Aswan, A; Sembiring, Sri Ulina Br (South Asian Journal of Social Sciences and Humanities, 2025)
The advancement of learning media for literature through web-based platforms and project based approaches is increasingly vital, aligning with the demands of 21st-century education,  which integrates Technological Pedagogical Content Knowledge (TPACK). This study  proposes the development of an interactive web-based electronic module as an innovative and  practical tool for literary education at both secondary and tertiary levels. The research adopts  a Research and Development (R&D) methodology, resulting in the creation of a web-based  electronic module tailored for the appreciation of prose fiction. This module includes  instructional content, interactive features, and project-based activities designed to enhance the  appreciation of Indonesian literary works. The feasibility of the module was evaluated in terms  of visual quality, content accuracy, software usability, and language clarity. Results indicate  that the module is effective and suitable as a medium for teaching and learning literary  appreciation. It offers significant contributions to the enhancement of digital learning tools in  the field of literature, fostering engagement and deeper understanding of fiction proses.
Keywords: digital learning tools; electronic modules; fiction prose appreciation; Indonesian literature; web-based electronic